Quantitative assessment of OCT and OCTA parameters in diabetic retinopathy with and without macular edema: single-center cross-sectional analysis - Cui, Yanyan; Feng, Dongfan; Wu, Changlong; Wang, Ping; Cui, Ruoxi; Wang, Xiaokun; Chang, Weiwei; Shang, Weiwei; Zhao, Bojun; Liu, Jing; Qin, Xuejiao (Frontiers in Endocrinology, 2024)
Aim The retinal and choroidal parameters were analyzed to understand the impairment of microcirculation of both retina and choroid in patients with diabetic retinopathy (DR). Methods Fifty-five treatment-naive non-proliferative diabetic retinopathy (NPDR) patients (75 eyes) with type 2 diabetes mellitus (T2DM), including 28 patients (36 eyes) with diabetic macular edema (DME) and 27 patients (39 eyes) without DME, and 25 healthy subjects (47 eyes) were enrolled in this study. The following parameters of DR patients with and without DME were evaluated: the foveal avascular zone area (FAZ-a), FAZ perimeter (FAZ-p), FAZ circularity index (FAZ-CI), total subfoveal choroidal area (TCA), luminal area (LA), stromal area (SA), choroidal vascularity index (CVI), choriocapillaris flow area percentage, superficial capillary plexus (SCP), and deep capillary plexus (DCP). Results SCP, DCP, and the percentage of choriocapillaris flow area were significantly different between DR patients with and without DME. The DR patients presented lower LA, CVI, and FAZ-CI compared to those of healthy controls (all p < 0.05). The percentage of choriocapillaris flow area in DR patients with and without DME was significantly lower than that in healthy controls (p < 0.05). SCP and DCP were significantly correlated with FAZ-a and FAZ-p but presented insignificant associations with FAZ-CI. Conclusions Optical coherence tomography (OCT) and OCT angiography (OCTA) parameters, such as LA, CVI, FAZ-CI, and the percentage of choriocapillaris flow area, were reduced compared to those in controls, indicating that the microcirculations of the retina and choroid in the macular area were impaired in DR patients with DME and without DME.